Green politics an A-to-Z guide - Mulvaney, Dustin (Thousand Oaks, Calif. SAGE, 2010)
This second volume in the SAGE Series on Green Society covers the availability and distribution of such resources as energy and how they impact economic development, domestic politics, and international cooperation and conflict.
"SAGE reference online."
Title from home page (viewed Jan. 24, 2011).
Mode of access: World Wide Web.
System requirements: Internet Explorer 6.0 (or higher) Firefox 2.0 (or higher).
Available as searchable text in HTML format.
Keywords: Green movement; Electronic books